Agenesis of a large number of permanent teeth after treatment of neonatal leukemia. Issue 4 (July 2015) - Tanaka, Hirokazu; Kurita, Hiroshi; Aizawa, Hitoshi; Kamata, Takahiro
Abstract The intensive treatment of hematological malignancy can cause dental abnormalities when applied during the period of dental and craniofacial development. Here, we report a case of absence of numerous teeth after treatment of neonatal leukemia. An 11-year-old boy was referred to our hospital complaining of delayed (no) eruption of many teeth. The patient had a history of neonatal acute monocytic leukemia. He had undergone systemic chemotherapy and allogeneic peripheral blood stem cell transplantation (PBSCT) during the period between 7 days and 9 months after his birth. Intraoral examination and a panoramic radiograph revealed absence of 25 of the permanent teeth (12, 13, 14, 15, 17, 18, 22, 23, 24, 25, 27, 28, 31, 32, 33, 34, 35, 37, 38, 41, 42, 44, 45, 47, and 48). Microdontia of the bilateral maxillary central incisors and right mandibular canine and taurodontism of the bilateral maxillary first molars were also observed. The developmental period of these affected teeth agreed with the period of chemotherapy and PBSCT.